Aktivitas Sosial-Keagamaan Pada Seni Relief di Das Pakerisan Dan Petanu, Gianyar, Bali - I Nengah Duija; Rema I Nyoman; I Wayan Yudhasatya Dharma (Institut Seni Indonesia Denpasar, 2022)
Gianyar has abundant archaeological remains from the prehistoric era, especially during the classical era. This can be seen from the cultural remains in the form of artifacts, eco-facts, sites, and others, reflecting the brilliant past of Gianyar civilization. This study aims to determine the socio-religious activities etched into the relief art in the Pakerisan and Petanu watersheds. The data was collected by observing relief artworks in the Pakerisan and Petanu watersheds, supported by relevant literature studies and in-depth interviews with key informants. This relief provides information on socio-religious life in ancient Bali, inspired by beliefs in ancestors, Buddhism and Shivaism accumulated in Shiva Siddhanta. This study resulted in findings in the form of socio-religious activities in the Pakerisan and Petanu watersheds. The socio-religious activities in question are mental development activities, exercising self-control, studying the nature of oneself and the universe, and using various worship media by choosing a location near a water source. This reflects the wisdom of the ancient Balinese era in maintaining harmony between various understandings, oneself, nature, and the Creator.